(untitled) (Journal of Academic Research, 2026)
Mathematical statistics underwent a major transformation during the last century with the discovery of shrinkage estimators, which provided an improved version of the classical tradition based on unbiased estimators. Since the discovery of Stein’s theory in the early 1960s, accepting a degree of bias has become an effective tool for reducing overall error and producing more stable estimators. This paper aims to provide a comprehensive review of the historical and theoretical development of shrinkage estimators, from the James-Stein model to modern models such as ridge regression, Least Absolute Shrinkage and Selection Operator (LASSO), and elastic net regression. It also focuses on their fundamental statistical basis and their growing role in the development of artificial intelligence (AI) and deep learning models. The paper concludes by presenting a unified vision that links statistical theory and modern intelligent applications by adopting shrinkage estimators as an integrated framework that combines mathematical precision with applied innovation in complex data environments. This unified framework illustrates how shrinkage estimators have evolved to become the cornerstone of intelligent predictive modeling.